2004
DOI: 10.5424/sjar/2004024-110
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variation and species relationships in a collection of Lens using RAPD and ISSR [Inter-simple sequence repeats]

Abstract: The genetic variation of a collection of twenty-two Lens accessions was assessed using RAPD and ISSR markers. The collection included accessions of the cultivated lentil, Lens culinaris ssp. culinaris, and its wild ancestor L. c. ssp. orientalis, and the other wild species of the genus: L. odemensis, L. ervoides, L. nigricans, L. tomentosus, and L. lamottei. Both types of markers produced a relatively high number of polymorphic markers in the whole collection, although the degree of variation within the cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 0 publications
1
17
1
3
Order By: Relevance
“…orientalis than to any other taxon, but it was distinguished by a hairy pod, a modified karyotype and cpDNA restriction pattern (van Oss et al 1997). Afterwards data of molecular analysis supported the independent species status of L. tomentosus (Galasso 2003;Sonnante et al 2003;Duran & Perez de la Vega 2004).…”
mentioning
confidence: 53%
“…orientalis than to any other taxon, but it was distinguished by a hairy pod, a modified karyotype and cpDNA restriction pattern (van Oss et al 1997). Afterwards data of molecular analysis supported the independent species status of L. tomentosus (Galasso 2003;Sonnante et al 2003;Duran & Perez de la Vega 2004).…”
mentioning
confidence: 53%
“…orientalis and L. odemensis are the most likely candidates to have constituted the main origin of extra-specifi c variability for the cultigens; however, more experimental proof is further needed. The genetic variability found with molecular markers seems to be low (Durán and Pérez de la Vega 2004 ;Sonnante et al 2003 ), suggesting a common origin for all the cultivated forms of lentil and a narrow range of achieved artifi cial selection. The observed differences detected among different geographical groups could be the plain result of a correlated response exerted by selection for higher yield, compared to a direct consequence of a more basic genetic difference.…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…The geographical pattern could simply be an indirect (correlated) response to different human selection approaches in different parts of the world accompanied with the usual sources of genetic variation (mutation, migration, and genetic drift) and crosses with companion weeds. In fact, molecular marker analyses have indicated that the genetic variability within cultivated lentil forms is relatively low (Durán and Pérez de la Vega 2004 ;Sonnante et al 2003 ), suggesting that the two great groups of cultivated lentils, microsperma and macrosperma , could only be variants for quantitative traits resulting from disruptive selection.…”
Section: Origin and Evolutionmentioning
confidence: 99%
“…ISSR have been used in many crop species including legumes (Bornet and Branchard, 2001;Rajesh et al, 2003), and have proved their usefulness in genetic mapping and marker assisted selection (Zietkiewicz et al, 1994). ISSR markers have already been used in lentil to evaluate genetic variation in collections of cultivated lentil by various researchers (Sonante and Pignone, 2007;Duran and Perez de la Vega, 2004). The present study was taken up to analyze the genetic diversity in different Lens spp., including both cultivated and wild species using ISSR markers .…”
Section: Introductionmentioning
confidence: 99%